PENGARUH PROMOSI DAN ELECTRONIC WORD OF MOUTH PADA MARKETPLACE BUKALAPAK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pengguna Marketplace Bukalapak) - Titania Putri Pangastuti; Ari Pradhanawati (Universitas Diponegoro, 2021)
Abstract: The consumptive lifestyle of today's society encourages many marketplaces to emerge. Bukalapak continues to improve service quality, but the intense competition makes Bukalapak's ranking and visits decrease every year, this indicates a decline in purchasing decisions at Bukalapak. The company's goal in improving service is to provide satisfaction and a good impression on consumers to make purchases, which are shown in several aspects such as promotion and electronic word of mouth. This study aims to determine: (1) the positive effect of promotion on the purchasing decisions at Bukalapak, (2) the positive effect of electronic word of mouth on purchasing decisions, (3) the positive effect of promotion and electronic word of mouth together on purchasing decisions. The type of the research is explanatory research using non-probability sampling and purposive sampling methods to which only consumers who have made purchases 3 times at Bukalapak in the past year. The number of samples in this study amounted to 100 respondents. The data collection method used in this research is a questionnaire compiled with a Likert Scale via google form then calculated using Microsoft Excel and SPSS for windows version 24 to test validity, reliability, correlation coefficient test, coefficient of determination, simple regression analysis, regression analysis multiple, significance test (t test and F test). The results of this study are: promotion and electronic word of mouth variabels have a significantly strong and positive effect either partially or simultaneously. Partially, promotions contributed 45.4% to purchasing decisions, while electronic word of mouth contributed 50.5% to purchasing decisions. Then simultaneously promotion and electronic word of mouth contributed 57.2% to purchasing decisions. It is recommended that Bukalapak increase their intensity of promotions to attract consumers in order to increase purchases. In addition, Bukalapak needs to improve their service quality and their rapid response in handling negative reviews by the consumer. Keywords: Promotion, Electronic Word of Mouth, Purchase Decision